Description of the Adult Male of Stylops nubeculae Pierce (Strepsiptera: Stylopidae), a New Record for Canada - Balzer, Zachary S.; Davis, Arthur R. (Zootaxa, 2020)
The morphology of the adult male of Stylops nubeculae Pierce, encountered in stylopized gasters of two adult bees of Andrena peckhami, is described for the first time. This species was previously known only from the endoparasitic adult female found in Colorado, USA. We report a new locality for this species in Alberta, Canada.